Measuring psychiatric patients satisfaction with the initial evaluation: A comparison of 2 measures. (March 2019) - Zimmerman, Mark; Mehring, Lucille B.; Moon, Sydney; Holst, Carolina Guzman
Highlight : As part of Maintenance of Certification (MOC), the American Board of Psychiatry and Neurology (APBN) developed a patient satisfaction form. We are not aware of any studies of the ABPN satisfaction survey. We compared the ABPN survey to the Clinically Useful Patient Satisfaction Survey (CUPSS). The psychometrics of the CUPSS were stronger, and it was preferred by patients as a measure of satisfaction with the initial evaluation. Abstract: As part of Maintenance of Certification (MOC) for physicians, the American Board of Psychiatry and Neurology (APBN) developed a patient satisfaction form. We are not aware of any studies of the ABPN satisfaction survey. The goal of the present study was to examine the psychometric characteristics of the ABPN survey, and to compare it to a satisfaction measure that was designed to assess satisfaction with the initial evaluation. Two hundred seven patients completed the APBN measure and the Clinically Useful Patient Satisfaction Scale (CUPSS) after their initial meeting with the psychiatrist. The patients also completed a questionnaire asking which of the two scales were better measures of satisfaction with the initial evaluation. The items on both scales were negatively skewed, and approximately 90% of the ratings on the APBN scale received the highest rating. Both scales had high internal consistency. All items were significantly correlated with indicators of global satisfaction. There was sufficient variability in satisfaction ratings to detect differences amongst clinicians. Significantly more patients indicated that the CUPSS was a better indicator of their satisfaction with the evaluation. The results of the present study raise some concerns about the ABPN measure. There was evidence of a ceiling effect, and this ceiling effect raises questions about the usefulness of the scale for the purposes of self-improvement. The psychometrics of the CUPSS were stronger, and it was preferred by patients as a measure of satisfaction with the initial evaluation.